“Walking on broken glass”: the changing nature of gendered constraints to career development and performance - Costa, Carlos (2015)
This paper investigates the often invisible barriers to women’s career development and performance, through systematic review of literature on gender and labour within organisations. The methodological approach used in this study consists of a thorough literature review of scientific papers collected, via the Online Knowledge Library (b-on). Although gender equality in the labour market is a generally perceived as a ‘win-win’ situation for organisations and society as a whole, several barriers are imposed to women’s career development, which are driven by theoretical misconceptions. Executive leadership is a role that is still particularly difficult for women to achieve. On the organisational level, an important contribution this paper makes relates to the identification and analysis of the barriers and sources of discrimination that affect women’s professional lives. Within the academic context, it acts as a wake-up call for researchers, to take additional care when addressing gender issues. This is because usage of inappropriate research methodologies creates knowledge that fails to represent women’s contemporary reality. The awareness of organisations regarding the benefits derived from having a gender-balanced workforce can be enhanced.